TREATMENT OF UROGENITAL INFECTIONS DURING PREGNANCY - Samadov Axror Axmadovich (World Scientific Research Journal, 2025)
Annotation: Urogenital infections (UGI) remain one of the urgent problems of obstetrics and gynecology. During gestation, UGI can cause complications such as chorioamnionitis, delayed intrauterine development and intrauterine and intranatal infection of the fetus, spontaneous miscarriages, premature birth, purulent-septic complications in the postpartum period. According to the literature, UGI in pregnant women is highly common and often occurs in a latent form, complicating their timely diagnosis and subsequent treatment.